Auctions versus posted prices in the revenue management of limited inventory. (4th November 2022) - Maslov, Alexander
Abstract: The paper examines a monopolistic seller with a limited inventory, who can sell it by auctions or posted prices in an online market. Previous studies have investigated a seller with unlimited inventory and found that selling by auctions and posted prices is the profit‐maximizing strategy. Contrary to this finding, for limited inventory, mixing selling mechanisms is not always optimal. In particular, when the number of risk‐neutral buyers is high, listing the inventory by auctions generates the highest profit. When faced with risk‐averse buyers, selling by posted prices and auctions is the best strategy. Posted prices are almost always inferior to other listing strategies.